Pengembangan Media “Fungo” Berbasis GeoGebra pada Materi Fungsi Kuadrat: Uji Validitas, Kepraktisan, dan Keefektifan - Laela Nur ‘Aini (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to develop a learning media named “Fungo” assisted by GeoGebra software for quadratic function material and to examine its validity, practicality, and effectiveness in improving students’ learning outcomes. This research employed the Research and Development (R&D) method using the 4-D development model, consisting of Define, Design, Develop, and Disseminate stages. The study was conducted in January 2026 at SMAN 2 Jember, involving 22 tenth grade students as research subjects. The research instruments included media validation sheets, pretest and posttest instruments, and student response questionnaires. Data were analyzed using validity analysis, practicality analysis, and effectiveness analysis through Paired Sample T-test and N-Gain calculation. The validation results indicated that the developed media achieved a mean validity score of 3.70 with the average of each score (𝑋) of 0.93, categorized as very high validity. The practicality test showed a percentage score of 94%, indicating that the media was practical. Moreover, the effectiveness analysis demonstrated a significant improvement in students’ learning outcomes, with N-Gain score of 0.73 (high category) and a significant difference between pretest and posttest scores (Sig. = 0.000 < 0.05). These findings suggest that the “Fungo” learning media assisted by GeoGebra software is valid, practical, and effective in enhancing students’ learning outcomes on quadratic function material and is suitable for implementation in mathematics learning. Keywords: learning media, GeoGebra, quadratic function, learning outcomes, research and development.
FINALISASI oleh Arif 2026 Juni 17
Keywords: learning media; GeoGebra; quadratic function; learning outcomes; research and development